Transforming rapeseed oil into fatty acid ethyl ester (FAEE) via the noncatalytic transesterification reaction. Issue 5 (1st November 2012) - Kwon, Eilhann E.; Yi, Haakrho; Jeon, Young Jae
<x xml:space="preserve">Abstract</x> A simple methodology for producing biodiesel is presented. The noncatalytic transesterification was carried out via the thermochemical process because the main driving force of biodiesel conversion was temperature rather than pressure. Noncatalytic transformation of rapeseed oil into fatty acid ethyl ester (FAEE) was performed in a continuous flow system under ambient pressure in the presence of activated alumina, charcoal, and carbon dioxide (CO2). The biodiesel conversion methodology introduced in this work enables the esterification of fatty acids (FFAs), and transesterification of triglycerides to be combined into a single process and leads to a 97.5 (±0.5)% conversion efficiency of biodiesel within 1 min at 420–500°C. The new process has high potential to achieve a breakthrough in minimizing the cost of biodiesel production owing to its simplicity and technical advantages. © 2012 American Institute of Chemical Engineers AIChE J, 59: 1468–1471, 2013